Mathematical Modeling of the Transient Processes in Propulsion System of the Upper Stage of the Cyclone-4M Launch Vehicle - PYLYPENKO, O.; DOLGOPOLOV, S.; NIKOLAYEV, O.; KHORIAK, N. (Science and Innovation, 2024)
Introduction. The development of the Cyclone-4M space launch vehicle (LV) by Pivdenne Design Offi ce is an important activity of the space industry of Ukraine. One of the LV innovations is feeding the liquid jet system (LJS) from the sustainer engine (SE) feedlines. Problem Statement. In order to implement the specifi ed method of the LJS feed, it is necessary to ensure the LJS operation during hydraulic shocks and pressure drops of the propellants during the SE start and shutdown. For this purpose, it is necessary to simulate the transient processes of the system start and shutdown. Purpose. The purpose is to estimate the parameters of the transient processes of the Cyclone-4M upper stage sustainer engine, given the eff ect of SE on the LJS, as a result of their joint operation. Material and Methods. The methods of the theory of automatic control, the impedance method, and the methods of numerical modeling of the unsteady motion of gas-saturated liquids have been used. Results. The transient processes in the joint (SE and LJS) propulsion system during the start and shutdown have been simulated. In the developed mathematical model, we have used dynamic gains of feedlines as distributed and concentrated parameter systems, which are reconciled in a certain frequency range. The SE start and shutdown have been calculated. The experimental and the calculated values of natural frequencies of fl uid oscillations, pressure peaks during hydraulic shocks, and the hydraulic shock patterns (horizontal pressure shelves when fluid continuity is broken) have shown a good agreement. Conclusions. A nonlinear mathematical model of the low-frequency dynamics of the upper stage of propulsion system of the Cyclone-4M LV has been developed and tested. The model can be used to predict the time dependences of the propellant pressure at the LJS inlet during the SE start and shutdown in extreme conditions of LJS operation in the joint (the SE and the LJS) feed system.